Basic Psychological Needs and Sports Satisfaction Among Brazilian Athletes and Coaches: The Mediating Role of the Dyadic Relationship - Contreira, Andressa Ribeiro; Nascimento Junior, José Roberto Andrade do; Caruzzo, Nayara Malheiros; Costa, Luciane Cristina Arantes da; Gaion, Patrícia Aparecida; Melo, Sandro Victor Alves; Fiorese, Lenamar (Frontiers in Psychology, 2019)
Sport satisfaction has been shown to be an important element for youth’s permanence in sport. Nonetheless, little is known about coaches’ sport satisfaction. Moreover, coach-athlete relationship is recognized as a fundamental element for sport success, however, it is currently unknown if its importance is similar for coaches and athletes. The present study investigated the mediating role of coach-athlete relationship in the association between satisfaction of basic psychological needs and sport satisfaction of Brazilian coaches and athletes. Subjects were 364 coaches and athletes, representing 182 dyads from different sports. The following instruments were used: Basic Needs Satisfaction Sport Scale (BNSSS), Coach-Athlete Relationship Questionnaire, athlete and coach versions (CART-Q) and the Athletic Satisfaction Questionnaire (ASQ). Data was analyzed through Structural Equation Modelling (SEM) with significance level at p<0.05. The results have shown that the mediating model for coaches did not present adequate fit while the direct model, without mediation, had adequate fit and explained 48% of sport satisfaction’s variance. For athletes, the mediating model has shown adequate fit and explained 81% of the sport satisfaction variance. Thus, it was concluded that the quality of coach-athlete relationship can be considered a determining factor for the satisfaction of young Brazilian athletes’ basic psychological needs as well as sport satisfaction, while being not as relevant for their coaches.